'You don't have the right to hit anyone': Domestic violence in Othello and Omkara. Issue 1 (1st August 2021) - Ridge, Kelsey
Alongside the infamous jealousy of Shakespeare's Othello lies the domestic violence that brings the play to its dark conclusion. Vishal Bhardwaj's 2006 Bollywood adaptation, Omkara, involves the same issues. The domestic violence, however, is present in different forms. It is a prominent part of Desdemona's plot arc and an important element of Emilia's backstory. Dolly's experience mirrors that of Desdemona. However, Indu's relationship with Langda is quite different from Emilia's relationship with Iago. These alterations lead Indu and Langda, though not Dolly and Omkara, to different outcomes from their Shakespearean counterparts. This article contrasts the depiction of domestic violence in Othello and Omkara and examines what is gained through the change in the appropriation.